(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The “holy fools” are suffering from “cretinism”, it is not intended as a physiological disease but it is rather a state of mind that allows them to be included in a certain category of artist. Then cretinism in this special meaning it is said to derive from the same etymological root as “Christian”, as a follower of Christianity, or that is from the French “Chrétien”. In this specific sense is therefore also includes a person so pure and naive to adhere to holiness and spiritual promise of eternal salvation by the religious profession of Christianity. An artist who believes deeply in his search for truth through art is for this reason identified as “holy”, in the same way a person who professed Christianity could be identified in a Christian artist, stupid and insane. About this concept of cretinism has been talk of holy fools in the case of artists such as Jerzy Grotowski and Carmelo Bene. The figure of the simpleton like an artist suffering from cretinism, in the sense that we have given here, then, is the topic of this paper. In particular here the artistic legacy of Carmelo Bene is discussed about his female heirs. The performer Lady Gaga will be analyzed as the most representative of the heirs of Bene, by the way of the song and video titled Judas; and by the entire album titled Born this way. Can be found in it figures as the Christ and his apostles and the chorus sings: “I’m just a holy fool.” Apart from that the poetic imagination and artistic vision are undoubtedly close to those of Bene.